(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Medical negligence in India is both a criminal offence under IPC and CR.P.C as well as a civil liability under the law of tort. If there is a violation of duty of care, civil responsibility normally involves a claim for damages in the form of compensation. It refers to a lack of caution in a situation when caution is required by law. When this responsibility is breached, a patient has the right to sue for negligence. Under the general law, civil culpability, i.e. monetary compensation, can be sought by pursuing a remedy before an appropriate Civil Court or consumer forum. Dependents of the deceased patient or the patient himself (if alive) file a lawsuit claiming civil culpability for the erring medical practitioner in order to obtain compensation.